Negative Poisson's Ratio Material Structure Based on 3D Printing and Its Application in Medical Field - Chongmin HUANG; Tianhai HUANG; Yonghua CHU (Zhongguo yiliao qixie zazhi, 2024)
First of all, the overall framework of 3D printing is briefly introduced, including the basic principles of the additive manufacturing process, the classification and summary of the seven processes. Secondly, the common negative Poisson’s ratio structure is introduced. Compared with the conventional structure, the negative Poisson’s ratio structure has stronger energy absorption capacity, better fracture resistance and better indentation resistance, which are its advantages in printing manufacturing. Finally, 3D printing, the application of negative Poisson’s ratio structure and the combination of the two are introduced from the different perspective of medical field, for example, the application of cardiovascular stent, biomedical material structure preparation, and lumbar disc implants. This paper suggests that the structural design of negative Poisson’s ratio in 3D printing guides the development of new application directions in the medical field. Negative Poisson’s ratio materials have a wide range of applications, not only in the medical field but also in mechanical equipment, automotive manufacturing, aerospace, and other high-tech industries.